INFLUENCE OF STORAGE TEMPERATURE ON VISCOSITY, COLOUR, EMULSION AND VITAMIN E STABILITY OF PINK GUAVA JUICE FORTIFIED WITH VITAMIN E - Mohamad Shahrimi Hashim; Faikah Awang @ Ismail, (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
This study was undertaken to assess the changes in viscosity, colour, emulsion stability, and vitamin E stability of pink guava juice fortified with vitamin E (PGJD) during 180 days of storage at 5°C, 15°C, and 25°C. PGJD with a combination of 70% (w/v) Xanthan Gum (XG), 30% (w/v) Carboxyl methyl cellulose (CMC), 0.8% (w/v) Polysorbate 80 (P80), and 225mg vitamin E was prepared and stored for 180 days at 5°C, 15°C, and 25°C. For every 30 days of storage, viscosity, emulsion, colour, and vitamin E stability were determined using a viscometer, chromameter, emulsion stability index (ESI), and high-performance liquid chromatography (HPLC), respectively. The result indicates that the viscosity of PGJD increased significantly slower when stored at a lower storage temperature. In addition, emulsion stability will be maintained for approximately 30 days longer when stored at a lower temperature as opposed to a higher temperature. The L* value of the colour increased for all samples, however, the C* values indicated red colour intensity from PGJD was gradually fading through time. In addition, the Ho value of all PGJD samples exhibited a steady increase during storage, whereas vitamin E exhibited a consistent deterioration pattern. The findings of the present study can be used as a guideline for beverage manufacturers and retailers in selecting the best storage temperature for their products.